Disease modeling and gene correction of LGMDR21 iPSCs elucidates the role of POGLUT1 in skeletal muscle maintenance, regeneration, and the satellite cell niche - Jose L. Ortiz-Vitali; Jianbo Wu; Nasa Xu; Annie W. Shieh; Nima Niknejad; Megumi Takeuchi; Carmen Paradas; Chunru Lin; Hamed Jafar-Nejad; Robert S. Haltiwanger; Sidney H. Wang; Radbod Darabi (Elsevier, 2023)
Autosomal recessive limb-girdle muscular dystrophy 21 (LGMDR21) is caused by pathogenic variants in protein O-glucosyltransferase 1 (POGLUT1), which is responsible for O-glucosylation of specific epidermal growth factor (EGF) repeats found in ∼50 mammalian proteins, including Notch receptors. Previous data from patient biopsies indicated that impaired Notch signaling, reduction of muscle stem cells, and accelerated differentiation are probably involved in disease etiopathology. Using patient induced pluripotent stem cells (iPSCs), their corrected isotypes, and control iPSCs, gene expression profiling indicated dysregulation of POGLUT1, NOTCH, muscle development, extracellular matrix (ECM), cell adhesion, and migration as involved pathways. They also exhibited reduced in vitro POGLUT1 enzymatic activity and NOTCH signaling as well as defective myogenesis, proliferation, migration and differentiation. Furthermore, in vivo studies demonstrated significant reductions in engraftment, muscle stem cell formation, PAX7 expression, and maintenance, along with an increased percentage of mislocalized PAX7+ cells in the interstitial space. Gene correction in patient iPSCs using CRISPR-Cas9 nickase led to the rescue of the main in vitro and in vivo phenotypes. These results demonstrate the efficacy of iPSCs and gene correction in disease modeling and rescue of the phenotypes and provide evidence of the involvement of muscle stem cell niche localization, PAX7 expression, and cell migration as possible mechanisms in LGMDR21.